Development of Village Applicant Capacity Training Model Based on Village Information System in Village Community Empowerment Department in Langkat District - Robinson Hutagaol; Abdul Hasan Saragih; Sahat Siagian (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
This study aims to: (1) produce an Addcie model for training the capacity of village apparatus based on village information systems, which is suitable for use in training the capacity of village officials (2) to determine the effectiveness of the Addcie model for training the capacity of village officials based on the village information system. This type of research is research and development using the R & D model from Borg and Gall combined with the instructional design model from Dick and Carey. The research method consists of two stages, namely stage I developing a training learning model and conducting trials, and stage II conducting product effectiveness testing. In the development and testing stage the product must go through a series of validation and trial processes. The results showed that (1) the material expert's assessment was very good, (82.94%), (2) the learning design expert's assessment was very good (81.58%), (3) the expert assessment of the learning model was on very good criteria (94.42%), (4) the assessment of media experts is in very good criteria (85%), (5) the assessment of individual trials is in very good criteria (81.03%), (6) assessment of small group trials is also in very good criteria (90.09%), (7) the assessment of limited field trials which are in very good criteria (92.08%).